2012
DOI: 10.1002/ange.201202118
|View full text |Cite
|
Sign up to set email alerts
|

Using an Electrical Potential to Reversibly Switch Surfaces between Two States for Dynamically Controlling Cell Adhesion

Abstract: Intelligente Oberflächen wurden hergestellt und charakterisiert, die zwei Arten von Molekülen tragen: anwuchsverhindernde Moleküle mit endständigen geladenen funktionellen Gruppen sowie Moleküle, die mit RGD‐Peptiden für die Zelladhäsion terminiert sind (siehe Bild). Durch Anlegen von Spannungen von +300 oder −300 mV konnten die Oberflächen zwischen zelladhäsiv und zellabweisend dynamisch geschaltet werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
(18 reference statements)
0
37
0
1
Order By: Relevance
“…It is easy to operate, fast, highly efficient, and also can be widely employed on different surfaces [20]. To efficiently control cell behavior, previous electrochemical approaches often involve to controlled reductive desorption of the Au-S bonds on surface by the application of a negative voltage, triggered electrochemically using of the hydroquinone/ quinone redox pair or switched a surface from hydrophilic to hydrophobic, etc., which then usually mediated the surface binding peptide sequence Arg-Gly-Asp (RGD) as recognition probe for cell adhesion [15,[21][22][23][24]. However, due to the longtime applied potential on surface [15] and irreversible formation or breaking of chemical bonds [21][22][23][24], an ultrasensitive electrochemical substrate for cell switching is highly required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to operate, fast, highly efficient, and also can be widely employed on different surfaces [20]. To efficiently control cell behavior, previous electrochemical approaches often involve to controlled reductive desorption of the Au-S bonds on surface by the application of a negative voltage, triggered electrochemically using of the hydroquinone/ quinone redox pair or switched a surface from hydrophilic to hydrophobic, etc., which then usually mediated the surface binding peptide sequence Arg-Gly-Asp (RGD) as recognition probe for cell adhesion [15,[21][22][23][24]. However, due to the longtime applied potential on surface [15] and irreversible formation or breaking of chemical bonds [21][22][23][24], an ultrasensitive electrochemical substrate for cell switching is highly required.…”
Section: Introductionmentioning
confidence: 99%
“…To realize such control, different functional substrates have been developed, where cell adhesion can be controlled in response to external stimuli, such as heat [9,10], chemicals [11], light [12][13][14], potential and enzymatic activities [15,16], etc. However, most of the stimuli-responsive substrate focuses on the single response till now, which would not satisfy the needs of double or multiple stimulation in future applications.…”
Section: Introductionmentioning
confidence: 99%
“…These switchable surfaces are playing an increasingly important part in the development of highly sensitive biosensors [85], novel drug delivery systems [148] and highly functional microfluidic [277], bioanalysis [278], and bioseparation [279] systems. Additionally, dynamic, synthetic surfaces that can control the presentation of regulatory signals [220,280] to a cell are expected to have a significant impact in tissue engineering [176] and regenerative medicine [208], and to provide unprecedented opportunities in fundamental studies of cell biology.…”
Section: Resultsmentioning
confidence: 99%
“…SPR has further shown that these responsive surfaces can control binding ability to greater than 90%. Following this work, Gooding and coworkers [220] have extended the concept of molecular mechanical motions of surface-bound electro-switchable molecules to control cell adhesion. The two-component SAMs comprised a protein-resistant hexa(ethylene glycol) (EG6) chain, which contained a charged moiety on its distal end, and a terminal RGD component on which cellular adhesion receptors, integrins, can bind (Fig.…”
Section: Samsmentioning
confidence: 99%
See 1 more Smart Citation